Associations between elevation, introduced red squirrels, and boreal bird distributions on Newfoundland - Ian G Warkentin; Jenna PB McDermott; Darroch M. Whitaker (Journal of Field Ornithology)
Elevational gradients in boreal forest songbird assemblages have received limited attention but may have important conservation implications in the face of climate change–induced habitat alteration and shifts in predator communities. Red squirrels ( Tamiasciurus hudsonicus ), introduced to Newfoundland in the 1960s and limited to lower elevations of the island, are important nest predators in boreal forests and influence bird assemblages where they are present. Our objectives were (1) to examine the role that elevation plays in the distribution of individual species, (2) to identify bird species for which occupancy rate was correlated with squirrel probability of occurrence, and (3) to investigate the influence of elevation and red squirrel occurrence on the species richness of different nesting guilds. We completed 1960 point count surveys for birds and red squirrels over two years across a 257 km² study area in western Newfoundland, Canada, which spanned southern boreal to northern boreal bioclimatic zones (75–610 m elevation). Among 28 species, eight had greater occupancy at higher elevations, 11 had decreasing occupancy with elevation, and nine showed no relationship. The relationship between red squirrel predicted occurrence and elevation was strongly negative. However, relationships between squirrel predicted occurrence and songbird occupancy varied by species, with occupancy for ten species being negatively related to squirrel probability of occurrence, and nine having squirrel occurrence as a better predictor of distribution than elevation. Richness of ground nesting species was best predicted by squirrel occupancy, but richness of above-ground and cavity-nesting species was best predicted by elevation. Populations of boreal birds in mountainous areas such as western Newfoundland are likely to show significant change and re-distribution in response to climate change as a function of altered forest composition and upslope expansion of red squirrels. Targeted monitoring of montane portions of the boreal forest is needed to assess responses to climate change by boreal songbirds.